A New Method for Simulating Power Flow Density Focused by a Silicon Lens Antenna Irradiated with Linearly Polarized THz Wave - Apriono, Catur; Rahardjo, Eko Tjipto; Hiromoto, Norihisa (UI Scholars Hub, 2015)
A terahertz system uses dielectric lens antennas for focusing and collimating beams of terahertz wave radiation. Linearly polarized terahertz wave radiation has been widely applied in the terahertz system. Therefore, an accurate method for analyzing the power flow density in the dielectric lens antenna irradiated with the linearly polarized terahertz wave radiation is important to design the terahertz systems. In optics, ray-tracing method has been used to calculate the power flow density by a number density of rays. In this study, we propose a method of ray-tracing combined with Fresnel’s transmission, including transmittance and polarization of the terahertz wave radiation to calculate power flow density in a Silicon lens antenna. We compare power flow density calculated by the proposed method with the regular ray-tracing method. When the Silicon lens antenna is irradiated with linearly polarized terahertz wave radiation, the proposed method calculates the power flow density more accurately than the regular ray-tracing.